Concentration of human capital, externalities and the wage gap in US metro areas. Issue 11 (1st November 2020) - Perez-Silva, Rodrigo; Partridge, Mark D.
ABSTRACT: The effects of the concentration of human capital on wages and productivity have been widely studied, but despite their heterogeneity, little attention has been paid to its effects on the wage gap. This paper assesses the impacts of human capital externalities on wages and on the US wage gap. The main results suggest a positive association between the share of high-educated workers and the wage gap between high- and low-educated workers. Moreover, the effect associated with the concentration of high-educated workers is entirely captured by changes in their wages, as wages of low- and medium-educated workers are statistically unaffected.